Proceedings of the 2019 on Designing Interactive Systems Conference 2019
DOI: 10.1145/3322276.3322361
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Design of Social VR Experiences with Older Adults

Abstract: There is growing interest in technologies that allow older adults to socialise across geographic boundaries. An emerging technology in this space is social virtual reality (VR). In this paper we report on a series of participatory design workshops that involved extended in-depth collaboration with 22 older adults (aged 70-81), that aimed to understand their views on the types of social VR experiences that they saw as being of value to older adults. This process culminated in a reminiscence-based social VR conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…Their participants identified four types of VR content they felt would be valuable to older users: travel; education; reminiscence; and self-care/therapeutic [32]. Similar preferences have been noted in other studies that have asked older adults about the types of VR experiences that they would like to see offered to older users [5]. The participants in the Roberts study expressed a "high level of interest in VR for the future" but criticised the system used in the study as they felt it made them "like a passive observer, rather than an active participant" saying they felt "inadequate social connectedness" [32, p.5-7].…”
Section: Vr and Older Adultssupporting
confidence: 59%
See 2 more Smart Citations
“…Their participants identified four types of VR content they felt would be valuable to older users: travel; education; reminiscence; and self-care/therapeutic [32]. Similar preferences have been noted in other studies that have asked older adults about the types of VR experiences that they would like to see offered to older users [5]. The participants in the Roberts study expressed a "high level of interest in VR for the future" but criticised the system used in the study as they felt it made them "like a passive observer, rather than an active participant" saying they felt "inadequate social connectedness" [32, p.5-7].…”
Section: Vr and Older Adultssupporting
confidence: 59%
“…In particular, they highlighted factors related to behavioural anthropomorphism, which refers to their embodied avatars' ability to speak, move, and act in a human-like manner, and other factors relating to the way the embodied avatars' non-verbal gestures were mapped in the prototype. In subsequent participatory design work, Baker and colleagues partnered with the same participants to produce a design concept for a social VR application that would respond to participants' communication needs [5].…”
Section: Amc In Social Virtual Worlds and Social Vr By Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They can also enjoy real-time face-to-face communication. voices, facial expressions, and actions [23,[31][32][33][34], without being affected by the natural environment and region. This can realize realistic social participation and improve safety.…”
Section: Advantages Of Vr Technology In Social Developmentmentioning
confidence: 99%
“…Moreover, Jie Li et al compared the photo sharing experience under social VR with Skype and Facebook spaces, and found that social VR was closer to face-to-face (F2F) sharing [32,35]. Baker et al [36] studied 22 elderly individuals to obtain their views on social VR in the form of a workshop, and suggested that social VR virtual items could trigger memories that could be shared with others, meeting their social needs [33]. These functions of VR are beyond the reach of other social applications, and provide a virtual public space that can improve the sense of social participation, ensure safety, and enhance mobility.…”
Section: Advantages Of Vr Technology In Social Developmentmentioning
confidence: 99%